Comparative analysis of in vitro accelerated glistening formation in foldable hydrophobic intraocular lenses - Tandogan, Tamer; Auffarth, Gerd U.; Choi, Chul Y.; Son, Hyeck Soo; Khoramnia, Ramin (International ophthalmology, 2021)
To analyse and compare the propensity to form glistenings in 4 different types of hydrophobic acrylic intraocular lenses (IOLs): Alcon AcrySof ® MA60AC, HOYA iSert® PC-60AD, Bausch&Lomb enVista, and Kowa Avansee™ PU6A.